Catalytic conversion of particle board over microporous catalysts - Choi, Suek Joo; Park, Sung Hoon; Jeon, Jong-Ki; Lee, In Gu; Ryu, Changkook; Suh, Dong Jin; Park, Young-Kwon (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
Catalytic pyrolysis of particle board, a type of waste wood that is increasingly produced all over the world, was carried out over three types of zeolite catalysts: HBETA, HZSM-5, and Ga-impregnated HZSM-5 (Ga/HZSM-5). Experiments conducted using a batch reactor showed that the bio-oil yield and gas yield in catalytic pyrolysis were lower and higher than those in non-catalytic pyrolysis, respectively. Analysis of the bio-oil using pyrolysis gas chromatography/mass spectrometry (Py-GC/MS) showed that the yields of high-value-added species such as aromatics and phenolics were increased to a large extent by catalytic upgrading, thus increasing the value of the product bio-oil. In particular, HZSM-5 exhibited high selectivity for aromatic compounds, and impregnation of Ga further increased the selectivity. HBETA could cause levoglucosans to decompose completely owing to its large pore size, resulting in increased yields of low-molecular-mass species. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: FAST PYROLYSIS; RADIATA PINE; ZEOLITES